REFORMASI SISTEM PENDATAAN WARGA NEGARA INDONESIA - Reni Windiani; Arif Sofianto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2012)
Data citizen to be one of important instrument in every policy and program, because through the data can be discovered potentials, capacities and needs required in successful development. There are two primary problems in the data nationals in Indonesia, are technically and substantively. Substantially there are errors of understanding that the population data became a base for the rights and obligations of citizens. While technically there are two main problems: First is data available from different agencies, less valid and less reliable due to weak systems, human resources and the carrying capacity of the technology. Second, there is no interconnection data among government agencies resulting in inefficiency and ineffectiveness, caused by ego respective sectoral government agencies, the interests of each sector and the absence of a firm policy from the government. The various steps that need to be done to make improvements is to reform the national data systems into a centralized and integrated with a firm policy support, human resource enhancement, improved tools of support, and interconnection policy data among government agencies.